LSD1 for the Targeted Regulation of Adipose Tissue - Li Chen; Xuan Sun; Daidi Chen; Qingjun Gui (Current Issues in Molecular Biology, 2022)
White and thermal (brown and beige) adipose tissue energy storage and oxidative regulation pathways play a central role in maintaining the energy balance throughout the body, and the dysregulation of these pathways is closely related to glucose and lipid metabolism disorders and adipose tissue dysfunction, including obesity, chronic inflammation, insulin resistance, mitochondrial dysfunction, and fibrosis. Recent epigenetic studies have identified the novel regulatory element LSD1, which controls the above parameters, and have provided new mechanistic possibilities for re-encoding the fate and function of adipocytes. In this review, we outline the current advances in adipocyte metabolism in physiology and disease and discuss possible strategies for LSD1 to alter the phenotype of adipose tissue and thus influence energy utilization to improve metabolic health.